Brand attitude and online repurchase intention of luxury products: A systematic literature review - Zhang, Tianyang; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Global Academic Excellence (M) Sdn. Bhd., 2025)
As technology continues to develop, e-commerce has penetrated into various fields. Among them, it has become very common that luxury brands have also started utilizing e-commerce to sell their products. Then, whether consumers' brand attitude has an effect on online repurchase intention is the focus of this study. Therefore, this systematic literature review investigates the relationship between brand attitude and online repurchase of luxury brands. Specifically, this study has two main objectives, namely, what is the relationship between brand attitudes and online repurchase intentions and what factors influence consumers' brand attitudes towards luxury brands. The study utilized the PRISMA protocol for systematic literature reviews, which was searched from two databases (Scopus and Web of Science). A total of 16 papers were included in this SLR, including three studies on brand attitude and online repurchase intention, 11 studies on luxury brands and brand attitude, and two studies on luxury brands and online repurchase intention. The findings show that most of the literature suggests that brand attitude is positively related to online repurchase intention and that the factors affecting brand attitude are mainly psychological.